Ichtyofauna as a Determinant ofWater Eco-Stress Factors - Jikia, Gogi; Lomtatidze, Zurab; Nikolaishvili, Marine; Koptonashvili, Lali (European Scientific Journal, ESJ, 2016)
Bacterial spread in fish gills and muscles with mesophilic aerobic and facultative-anaerobic microorganisms. These microorganisms are caught in 4 points of the river Alazani which depends on seasonal eutrophication of the water ecosystem. It also depends on the existence of microorganisms. In summer months when water gets warm and, at the same time, chemical and fecal masses flow into the water, the amount of microorganisms increase. As the temperature of the water decreases towards autumn-winter, rains increases which leads to reservoirs dilution and decrease in organic substances. They mostly occur in suspended condition and their amount in water decreases and thus in fish gills and muscles.